Active learning: using crossword and wordsearch puzzles for teaching vocabulary to students of the medical faculty (Eurasian Journal of Philology Science and Education, 2024)
Vocabulary teaching is an essential part of the professionally-oriented foreign language teaching and learning process. The teaching community always strives to enhance the teaching tools and introduce new ones to make the learning process more active and learner-centered. The potential pedagogical value and effectiveness of crossword and wordsearch puzzles were explored in many studies. This work considers crossword and wordsearch puzzles as pedagogically useful resources for teaching vocabulary to students majoring in “General Medicine”. This study was carried out at the Medical Faculty of the al-Farabi Kazakh National University in groups GM 22-05 and GM 22-06. Fifteen international students enrolled in a foreign language course participated in this study. During the whole academic semester, students were given crossword puzzles as an additional teaching tool for learning and testing the knowledge of the new vocabulary and wordsearch puzzles for practicing vocabulary as fillers or integrated learning activity. The survey results showed that students had a positive experience and were eager to learn and practice vocabulary via solving crossword and wordsearch puzzles. The findings revealed that crosswords can be beneficial and helpful for (a) teaching and learning new vocabulary; (b) testing students’ knowledge of the studied vocabulary; (c) teaching spelling; (d) enhancing students’ analytical and cognitive skills as well as (e) relieving stress and giving students a feeling of accomplishment. While wordsearch puzzles are useful for teaching and learning new vocabulary, particularly their spelling, in a playful manner. Both tools can be used by English language teachers as a creative learning material for teaching vocabulary in an interesting, engaging and fun way. In the practical part of the research, pedagogical suggestions for the creation and use of crossword and wordsearch puzzles are provided.Key words: foreign language teaching, English for professional purposes, teaching vocabulary, active learning, gamification, crossword puzzles, wordsearch puzzles